Propuesta de alternativas de solución al problema de tratamiento de aguas duras en ISLA SALAMANCA (2022)
70% of the human body is represented by water, currently guarantees the right of citizens to consumption of this vital element, but the reality that often remains demonstrated there are, families that do not count with drinking water, which must carry out a journey to get it.